Minimally invasive buried guidance combined with stable orbital septal fat fixation for correction of tear trough-associated lower eyelid bags: application and outcomes - Zhang, Qiang; Min, Fangjian; Xia, Hongfu; Gao, Chong; Song, Jie; Jin, Lei; Liu, Wang (Frontiers in Medicine, 2025)
BackgroundTraditional transconjunctival lower blepharoplasty procedures that remove only the orbital septal fat often fail to effectively correct tear trough deformities, and may even exacerbate lower eyelid hollowness. Thus, developing a comprehensive surgical technique that can simultaneously correct both eye bags and tear troughs holds great clinical significance.ObjectiveThis study aimed to evaluate a modified transconjunctival lower blepharoplasty technique that incorporates orbital fat repositioning and minimally invasive buried-guiding fixation to simultaneously correct eye bags and tear trough deformities. The goal was to restore a youthful contour of the lower eyelid and assess the clinical efficacy and safety of this approach.MethodsThis study was designed as a prospective, single-center cohort study. A total of 30 patients (3 males, 27 females; mean age: 28 years) with lower eyelid bags and tear trough deformities were enrolled in this study. These patients were treated at the Department of Plastic Surgery, Affiliated Hospital of Yangzhou University, between January 2022 and December 2024. All patients underwent transconjunctival lower blepharoplasty combined with a buried-guiding fixation technique to perform strong orbital fat anchoring and correct both deformities.ResultsAll 30 procedures were successfully completed with primary healing achieved. The average follow-up period was 6.2 months (ranging from 3 to 12 months). Postoperative outcomes showed significant improvement in both lower eyelid bags and tear troughs, with a more youthful midface appearance and no external scarring. Patient satisfaction was high.